How Not to Miss the Mild Forms of Mucopolysaccharidosis Type I in Patients With Articular Manifestations of the Disease? - Natalia V. Buchinskaya; Mikhail M. Kostik; Oksana L. Kolobova; Larisa N. Melnikova (Вопросы современной педиатрии, 2019)
Mucopolysaccharidosis type I (MPS I) is a hereditary metabolic disease that manifests itself in childhood by systemic damage to tissues and organs, a constantly progressive course leading to disability. Diagnosis of mild forms of the disease is particularly difficult due to the absence of specific symptoms. A specific symptom of the mild forms of MPS I (as for other types of MPS) is joint stiffness in children combined with hernia, frequent infections, or valvular defects. Stiffness in MPS I is often interpreted as a manifestation of rheumatological diseases (arthrogriposis, juvenile idiopathic arthritis). The article offers a simple algorithm for diagnosing MPS I, which helps to eliminate the disease using a simple test for determining the activity of an enzyme called alpha-L-iduronidase in a dried blood spot.